Knowledge, attitudes, and practices of registered dietitians and nutritionists regarding enteral and parenteral nutrition support in Ghana: a needs assessment study - Ayande, Ruthfirst E. A.; Agordoh, Percival D.; Salino, Vanessa J.; Webster-Ariyan, Clarisa; Collier, Lindsay; Asante, Matilda; Carbone, Elena T. (Frontiers in Nutrition, 2023)
Background There is a paucity of data on enteral and parenteral (EN and PN) nutrition support (NS) provided by nutrition and dietetic practitioners in adult acute care settings in Ghana. Furthermore, gray literature suggests that Ghanaian clinical nutrition professionals (CNPs) are seldom involved in advanced nutrition care teams. Objectives To assess the knowledge, attitudes, and practices of Ghanaian CNPs regarding EN and PN. Methods An online cross-sectional survey was administered to Ghanaian CNPs ahead of a professional development workshop on EN and PN Support. Participants were asked questions about initiation and timing of NS, and knowledge on availability of commercial formula. A 5-point Likert scale was used to assess self-efficacy in using EN and PN. To assess practical knowledge on EN and PN, participants were asked to identify whether EN or PN was indicated for seven short case scenarios. Open-ended questions were used to assess reasons for participant self-ratings. Results A total of 76 dietitians, nutritionists, students, and interns completed the survey. For EN, self-efficacy scores were lowest for the calculation of enteral goal rate, and goal volume (mean 3.20 ± 1.27), and writing of EN prescriptions (mean 3.07 ± 1.29). Self-efficacy scores for the formulation of alternative formulas in lieu of commercial formula were the highest (3.63 ± 1.36). For PN, self-efficacy scores for all domains were lower than 3, with the lowest scores observed for writing PN prescriptions (2.19 ± 1.14) and determining micronutrient additives (2.12 ± 1.04). We identified limited training and lack of practical exposure to NS, limited ability to effectively monitor tube feeds, and prohibitive cost and limited availability of EN and PN formula among the barriers impacting self-efficacy scores. Conclusion Given the vital role that CNPs play in the delivery of EN and PN, it is important to develop professional training programs especially focused on PN to bridge knowledge and practice gaps.